Analysis of fault in power transformer by using dissolve gas analysis / Azizul Firdaus Mahmor - Mahmor, Azizul Firdaus (2013)
Transformer is an equipment that transform power from one circuit to another circuit without changing any frequency but different in voltage level. Power transformer will successfully function depends on component which are in their consistent thermal and electrical stress. There is many type of fault occur in transformer which is arcing, partial discharging and overheating. All this type of fault can be traced by using Dissolve Gas Analysis Techniques. The main function of Dissolve Gas Analysis Techniques is to analyze and differentiate the type of electrical faults in transformer. Different gas level in the transformer oil that produced by the breakdown occur in the transformer oil will detected by Dissolve Gas Analysis.